Impact of Encryption on Qos in Voip - Radmand, Pedram; Talevski, Alex (IEEE Computer Society, 2010)
This paper studies the impact of different encryption algorithms on the quality of Voice over Internet Protocol (VoIP). Assuring Quality of Service (QoS) is one of the primary issues in any IP based application that examines the voice quality of VoIP. This paper examines QoS in terms of lost packet ratio, latency and jitter using different encryption algorithms along with firewalling at the IP layer. The results of laboratory tests indicate that the impact on the overall performance of VoIP depends upon the bandwidth available and encryption used. Findings include the need for the provision of bandwidth for encryption, and even when adequate bandwidth is provided encryption algorithms can increase lost packet ratios and packet latency, and reduce.Overall, the results indicate the implementation of encryption algorithms may degrade the voice quality even if bandwidth is adequate.